Anatomic Total Shoulder Arthroplasty with All-Polyethylene Glenoid Component for Primary Osteoarthritis with Glenoid Deficiencies - Frederick A. Matsen, III, MD; Anastasia J. Whitson, BSPH; Jeremy S. Somerson, MD; Jason E. Hsu, MD (JBJS Open Access, 2020)
Background:. This study evaluated the ability of shoulder arthroplasty using a standard glenoid component to improve patient self-assessed comfort and function and to correct preoperative humeral-head decentering on the face of the glenoid in patients with primary glenohumeral arthritis and type-B2 or B3 glenoids. Methods:. We identified 66 shoulders with type-B2 glenoids (n = 40) or type-B3 glenoids (n = 26) undergoing total shoulder arthroplasties with a non-augmented glenoid component inserted without attempting to normalize glenoid version and with clinical and radiographic follow-up that was a minimum of 2 years. The Simple Shoulder Test (SST), the percentage of humeral-head decentering on the glenoid face, and bone ingrowth into the central peg were the main outcome variables of interest. Similar analyses were made for concurrent patients with type-A1, A2, B1, and D glenoid pathoanatomy to determine if the outcomes for type-B2 and B3 glenoids were inferior to those for the other types. Results:. The SST score (and standard deviation) improved from 3.2 ± 2.1 points preoperatively to 9.9 ± 2.4 points postoperatively (p < 0.001) at a mean time of 2.8 ± 1.2 years for type-B2 glenoids and from 3.0 ± 2.5 points preoperatively to 9.4 ± 2.1 points postoperatively (p < 0.001) at a mean time of 2.9 ± 1.5 years for type-B3 glenoids; these results were not inferior to those for shoulders with other glenoid types. Postoperative glenoid version was not significantly different (p > 0.05) from preoperative glenoid version. The mean humeral-head decentering on the glenoid face was reduced for type-B2 glenoids from −14% ± 7% preoperatively to −1% ± 2% postoperatively (p < 0.001) and for type-B3 glenoids from −4% ± 6% preoperatively to −1% ± 3% postoperatively (p = 0.027). The rates of bone integration into the central peg for type-B2 glenoids (83%) and type-B3 glenoids (81%) were not inferior to those for other glenoid types. Conclusions:. Shoulder arthroplasty with a standard glenoid inserted without changing version can significantly improve patient comfort and function and consistently center the humeral head on the glenoid face in shoulders with type-B2 and B3 glenoids, achieving >80% osseous integration into the central peg. These clinical and radiographic outcomes for type-B2 and B3 glenoids were not inferior to those outcomes for other glenoid types. Level of Evidence:. Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.